Teaching marketing to a group of international students: a case study - Xara-Brasil, Duarte (2019)
Trabalho apresentado em 11th Iberoamerican Academy of Management Conference, Bogotá, Colômbia, 4-6 de dezembro 2019, Bogotá, Colômbia